Analisis Kepuasan Pelanggan Terhadap Kualitas Layanan Aplikasi Flavour Fog Menggunakan Metode PIECES - Natasha Maya Djaja; Ahyar Muawwal; Marlina (KHARISMA Tech, 2023)
Flavor Fog is a mobile-based application designed to help the problems of e-cigarette users or what is often called vaping. Flavor Fog is built by having several main features including being able to order products or goods online, and several other features. The main goal of the researcher is to develop the Flavor Fog application better, therefore it is necessary to analyze the user satisfaction of the Flavor Fog application. By doing user satisfaction analysis, researchers can find out what needs to be improved and improved in the application. In this study, researchers used the PIECES method to analyze the level of user satisfaction, by conducting validity tests, reliability tests, and PIECES calculation tests. Collecting data through distributing questionnaires with 19 questions to users of the Flavor Fog application. The results of this study include 6 PIECES variables, namely Performance, Information, Economics, Control and Security, Efficiency, Service with all answers in the satisfied category.